Pemberian Insentif kepada Grup Karyawan Berdasarkan Kompetensi Spencer - Ngatilah, Yustina (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
Knowing that success in the implementation of the strategy implemented by management to achieve the vision and mission that has been established, it would require an appropriate measure of performance using a design with two Spencer competence perspectives measurement comprehensibly and integrated that is in each criterion is expected to concretely describe the performance of the company and can be used as a measure of judgment in the provision of incentives. This study aims to support the decision to give incentives to the grup of employees with competency-based Spencer and Analytic Hierarchy Process as a weighting in the decision-making strategy to improve company performance. Based on the results of performance measurement in companies using the Sakti PT.Biru Spencer and Analytical Hierarchy Process can be concluded that the employee grup A has a value of 3.516 of performance achievement., grup B has a value of employee performance achievements 3.059, grup C has a value of employee performance achievements 3.138, grup D employee has a value of 3.57 and the achievement of performance grup E employees have a value of 3.563 of performance achievement. The results of measurements of the performance of each grup of employees by using the method of Spencer and AHP, are known to facilitate the performance of each grup and the management in providing the right incentives, the amount of incentives that should be given to each work grup performance based on achievement during the first 3 months in 2009, where employee grup B the highest incentives of Rp 6,153,907, -, grup D employees of Rp 6,113,469, -, grup of employees amounting to Rp 5,845,617 A, grup C of Rp 3,669,158 employees and employees of grup B of Rp 3,217, 850